MUNICIPAL MANAGEMENT AND NEIGHBORHOOD PARTICIPATION IN THE RESIDENTS REPRESENTED IN THE DISTRICT OF CHILCA - HUANCAYO - Chávez Epiquén, Abdías (2019)
The objective was to determine the relationship between municipal management and neighborhood participation in the residents represented in the 2017 Chilca District Municipality. The research, by its nature, was of a theoretical basic type, the scientific and quantitative methods were applied, with a design descriptive correlational, for the sample was taken to 120 representatives of the organized civil society of the District Municipality of Chilca. We used the survey technique and the questionnaire instrument, on the variable municipal management and neighborhood participation. The investigation concluded that there is a direct relationship between weak municipal management and neighborhood participation in the residents represented in the Chilca District Municipality 2017, with a "rho" coefficient of Spearman 0.383, at a level of significance of 5%; and t = 4.79; to efficient municipal management a favorable neighborhood participation. KEYWORDS: Municipal management, local participation, relation.